PERBANDINGAN METODE PREFERENCE SELECTION INDEX (PSI) DENGAN METODE SIMPLE ADDITIVE WEIGHT (SAW) PADA PEMILIHAN MANDOR TERBAIK PADA PT AGRO MUKO - Nurul Husna; Reno Supardi; Yupianti Yupianti (Teknosia, 2021)
PT.Agro Muko is a Foreign Investment Company engaged in oil palm and rubber plantations. Administratively, PT. Agro Muko is located in several sub-districts, namely North Mukomuko District, South Mukomuko District, Lubuk Pinang District, Teras Terunjam District, Pondok Suguh District, V Koto District, Penarik District, Selagan Jaya District, Air Dikit District and Teramang Jaya District, Bengkulu Regency. north.For this reason, the author tries to build an application that compares the preference selection index (psi) method with the simple additive weight (saw) method on the selection of the best foreman using the Preference Selection Index (PSI) method using Visual Basic Net, in order to facilitate PT Agro muko in selecting best employee every year